Stress-dependent dielectric and ferroelectric properties of sol-gel-derived PZT/WO3 ceramics - Sreesattabud T. (2014)
In this study, PZT/xWO3 (where x=0, 0.5, 1 and 3wt.%) ceramics were prepared from powders derived from a triol sol-gel process. The powders were pressed and sintered at 1100 °C for 6 h. Phase characterization by XRD indicated that the concentration of WO3 affected the content of tetragonal and rhombohedral phases. The ferroelectric and dielectric properties of the ceramics were determined under compressive stress in the range of 0-130 MPa. The ferroelectric properties were reduced with increasing stress. Stress-induced domain wall motion suppression and non-180° ferroelectric domain switching processes were responsible for the changes observed for ferroelectric parameters. In addition, the dielectric constant was found to increase with stress, which could be explained by a change in domain structures and the de-aging phenomenon. © 2010 The Royal Swedish Academy of Sciences.